METAPHISICAL BACKGROUND OF TECHNOLOGY - D. Y. Snitko (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to clarify the nature of the connection of philosophy of both metaphysics and science-technical knowledge, the technology itself. To study the problem of relations between scientific and technical thinking, and metaphysics the author tries to clarify the nature of the scientific and technical thinking, analyze the appropriateness of instrumental or ontological approaches for understanding technology and its metaphysical foundations. Methodology of this work consists of such intellectual approaches as the phenomenological, hermeneutic and comparative methods. Originality. The originality of the article is in the clear question about the metaphysical preconditions of technology, firstly made in the national literature. In addition, the author in a well-argued manner proves that the phenomenon of technology is based on the metaphysical structures of being and the human mind, despite the fact that technologies are closely related to the empirical world. Apart the well-known thesis on the relationship of technology and art, the author insists on such precondition technologies as the human's ability of the transcendence and the presence of aprior forms of space and time that are the basis of any design, in human's brainwork. Moreover, it is demonstrated that modern technology in the context of studies of quantum physics reveals a new way of being of vehicles (artifacts), that lost not only the empirical, but also practical, instrumental measurements. Conclusion. The study found that the formation of technology as a phenomenon is closely related to metaphysical structures of being and human brainwork. Particularly, the author focuses on the following assumptions technology as the person's ability to transcend and presence of mind of a priori forms of time and space. Based on these arguments, one can make conclusion about the limitations of purely instrumental (pragmatic) interpretation technology and emphasize the metaphysical premises equipment and metaphysical aspects of modern technology, and the important role of philosophy in these problems.